2011
DOI: 10.1007/s00431-010-1362-9
|View full text |Cite
|
Sign up to set email alerts
|

N-carbamylglutamate treatment for acute neonatal hyperammonemia in isovaleric acidemia

Abstract: Hyperammonemia occurs mainly in patients with branched-chain organic acidemias such as propionic, methylmalonic, and isovaleric acidemias. Its pathophysiological process is mainly via the competitive inhibition of N-acetylglutamate synthetase. Oral carglumic acid (N-carbamylglutamate) administration can correct hyperammonemia in neonates with propionic and methylmalonic acidemias, thus avoiding dialysis therapy. Isovaleric acidemia is an autosomal recessive disease of leucine metabolism due to deficiency of is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 10 publications
0
26
0
2
Order By: Relevance
“…This is the situation in some organic acidurias [26][27][28][29][30] or in valproate-induced hyperammonemia [31] and might also be the case in fatty acid oxidation disorders.…”
Section: Drug Profilementioning
confidence: 96%
See 1 more Smart Citation
“…This is the situation in some organic acidurias [26][27][28][29][30] or in valproate-induced hyperammonemia [31] and might also be the case in fatty acid oxidation disorders.…”
Section: Drug Profilementioning
confidence: 96%
“…Hyperammonemia in organic acidurias is thought to be caused in part by inhibition of NAGS due to accumulation of toxic intermediates and by deficiency of glutamate or acetyl-CoA as the substrates of NAGS (Table 1) [26,29,30,[49][50][51][52][53].…”
Section: Biochemistry and Metabolismmentioning
confidence: 99%
“…Kasapkara et al [15] reported on the use of NCG in the treatment of hyperammonaemia in a 3-day-old neonate with decompensated isovaleric aciduria with a single dose of NCG 150 mg/kg. Plasma ammonia levels decreased from 568 µg/dl (333.4 µmol/l) to 72 µg/dl (42.3 µmol/l) in 6 h. Studies have demonstrated that NCG enhances ureagenesis and reduces ammonia in organic acidurias presumably by increasing flux through the carbamoyl phosphate synthetase 1 reaction in the urea cycle [16].…”
Section: Discussionmentioning
confidence: 99%
“…NCG has recently been used as part of a multiple treatment strategy for hyperammonaemia in MMA [5,6,7] and in other classical organic acidurias such as propionic aciduria [6,7,11,12,13,14] and isovaleric aciduria [15]. Kasapkara et al [15] reported on the use of NCG in the treatment of hyperammonaemia in a 3-day-old neonate with decompensated isovaleric aciduria with a single dose of NCG 150 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Sumado al tratamiento clásico, disminuye de forma rápida los niveles de amoniaco en plasma y en muchas ocasiones evita la necesidad de hemodiálisis o diálisis peritoneal (20). Hasta hace poco, la NGG se utilizaba solo después del fracaso del tratamiento clásico; no obstante, diferentes autores han recomendado administrar este fármaco para los recién nacidos tan pronto como se detecten severos episodios de hiperamoniemia de causa aún no conocida (20)(21)(22) y actualmente es un fármaco de primera línea en los protocolos (23).…”
Section: Amoniounclassified